Creative accounting - innovation or fraud? - Okarma, Klaudia (SPC Journal of Education, 2020)
The aim of this article is presentation of typical issues that concern definition and interpretation of the nature of creative accounting, and also difficulties faced with differentiation between creative accounting and book-keeping fraud. Historical and contemporary views as well as own interpretation of creative accounting have been proposed.Â